Communication difficulties and alternative ways for effective communication in critically sick patient in ICU - Mamta Verma; Vandana Pakhide; D Sharad Gedam (International Journal of Medical Research and Review, 2022)
Inability to communicate can be a distressing problem for the patient who may be unable to speakbecause of the use of the paralyzing drugs or the endotracheal tube. Communication is the essenceof human life. Communication difficulties in intensive care units (ICU) with critically ill patients havebeen well documented for more than three decades. Critical care nurses provide a high level ofskilled nursing for total patient care and often facilitate communication between all of the peopleinvolved in the care of the patient. As part of any procedure, the nurse should explain what willhappen to the patient when the patient cannot speak. The nurse should explore alternative methodsof communication including the use of devices such as picture boards, note pads, magic slats, orcomputer keyboards when speaking with the patient. The nurse can assist the patients and familywith their feeling of anxiety by encouraging them to express concerns, ask questions, and state theirneeds.Methods: For the present review article collected a database from studies that reportedcommunication difficulties with patients admitted in intensive and critical care units because ofmechanical ventilation, tracheostomy, paralyzing drugs or invasive procedures, and studies relatedto methods of improving communication strategies for the patient in the critical care unit.Result:Results suggests that most alternative methods of communication were effective in improvingpatient satisfaction, decreasing patient frustration and facilitating communication. This review articleis aimed that critical care nurses assessing communication needs; identifying appropriate alternativecommunication strategies; create a customized care plan with the patient, the patient’s family, andother health care team members. The present review article focuses on the importance of effectivecommunication between critical care nurses and patients and between all of the people involved inthe care of the patient.